2007
DOI: 10.1097/iae.0b013e3180ed458d
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Bevacizumab Injections for Treatment of Central Retinal Vein Occlusion

Abstract: Intravitreal injection of bevacizumab appears to be a new treatment option for patients with macular edema secondary to CRVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 40 publications
4
81
1
2
Order By: Relevance
“…6,7,[9][10][11][12][13][14][15][16][17][18][19] The two major side effects of the intravitreal triamcinolone were a steroid induced increase in intraocular pressure and development of cataract. [21][22][23][24][25] In contrast, studies on intravitreal bevacizumab by Rosenfeld et al and other researchers showed an improvement in visual acuity, reduction in macular thickness, and only minor complications in patients with CRVOs, [26][27][28][29][30][31][32][33][34] so that intravitreal triamcinolone was rapidly exchanged by intravitreal bevacizumab for the treatment of CRVO. It agrees with this study, in which the best-corrected visual acuity improved significantly in the triamcinolone group and in the bevacizumab group with a no statistically significant difference in the gain in visual acuity between both study groups, although the reduction in macular oedema was slightly more pronounced in the triamcinolone group (Table 2) (Figure 1).…”
Section: Discussionmentioning
confidence: 96%
“…6,7,[9][10][11][12][13][14][15][16][17][18][19] The two major side effects of the intravitreal triamcinolone were a steroid induced increase in intraocular pressure and development of cataract. [21][22][23][24][25] In contrast, studies on intravitreal bevacizumab by Rosenfeld et al and other researchers showed an improvement in visual acuity, reduction in macular thickness, and only minor complications in patients with CRVOs, [26][27][28][29][30][31][32][33][34] so that intravitreal triamcinolone was rapidly exchanged by intravitreal bevacizumab for the treatment of CRVO. It agrees with this study, in which the best-corrected visual acuity improved significantly in the triamcinolone group and in the bevacizumab group with a no statistically significant difference in the gain in visual acuity between both study groups, although the reduction in macular oedema was slightly more pronounced in the triamcinolone group (Table 2) (Figure 1).…”
Section: Discussionmentioning
confidence: 96%
“…However, only nonischaemic eyes showed statistically significant visual acuity improvement at each time point. Priglinger et al 41 reported that the efficacy of intravitreal bevacizumab was similar between non-ischaemic CRVO and ischaemic CRVO. However, ischaemic CRVO was associated with significantly lower visual acuity than nonischaemic CRVO (Po0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there have been other reports of shortterm beneficial effect of intravitreal bevacizumab to treat macular oedema secondary to retinal vascular disease, including central retinal vein occlusion 31,32 and diabetic retinopathy. 33,34 Gü ndü z et al 20 reported a dramatic improvement in the visual acuity with significant macular thickness reduction after intravitreal bevacizumab injections (1.25 mg/0.05 ml) for patients with BRVO.…”
Section: Discussionmentioning
confidence: 99%